Pengaruh Penggunaan Dan Respons Chatbot Terhadap Kepuasan Konsumen E-Commerce - Takaria, Zifora Yanesya; Tjokrosaputro, Miharni (Jurnal Ekonomi, 2024)
The development of technology and innovation impacts the growth of e-commerce activities and continues to expand yearly. This growth has led to an increased demand for efficient customer service. One effort made by e-commerce companies is to implement chatbots in their customer service. This study aims to analyze the impact of chatbot usage and response on e-commerce customer satisfaction, with mediation by extrinsic and intrinsic values of the online consumer experience. Data were collected by distributing questionnaires, and 213 respondents from several cities in Indonesia were successfully gathered. The data were processed using Smart PLS 3 software. This study demonstrates that chatbot usage and response, mediated by extrinsic and intrinsic values, positively affect customer satisfaction.